UPAYA MENINGKATKAN KEMAMPUANPEMECAHAN MASALAH MATEMATIKA MENGGUNAKAN MODEL PROBLEM SOLVING DI MI NURUL FALAH - Rosfiani, Okta; Wardoyo, Verrel Attarik; Fajriani, Nurul; Putri, Nayaka Zahrani; Heryana, Rafi Muzaki (FKIP Universitas Al Washliyah Medan, 2025)
Efforts to improve mathematical problem solving abilities at MI Nurul Falah are important considering the challenges students face in understanding mathematical concepts. the problem solving model was chosen as an effective approach to help students develop critical and creative thinking skills in solving mathematical problems. by applying this model, it is hoped that students will not only be able to solve mathematical problems but also understand the processes involved in solving these problems. this research was conducted at MI Nurul Falah involving 25 class II students. in this research, students were given a series of tests and assignments designed to measure their mathematical problem solving abilities before and after implementing the Problem Solving Model. The research process consists of two cycles, where each cycle includes planning, implementation, observation and reflection The approach used in this research is Classroom Action Research (PTK) which focuses on the application of the Problem Solving Model. Data is collected through observations, problem-solving ability tests, and interviews with students to obtain feedback about their learning experiences. Data analysis was carried out by comparing test results before and after implementing the model. The results showed a significant increase in students' mathematical problem solving abilities. After implementing the Problem Solving Model, the percentage of students who achieved the Minimum Completeness Criteria (KKM) increased from 36% to 88%. This shows that the model is effective in improving students' mathematical problem solving skills at MI Nurul Falah.